A MORE DEVASTATING VERSION OF THE RAVEN PARADOX. Issue 54 (2020) - Sayan, Erdinç
Abstract : Hempel's famous Raven Paradox derives from Nicod's criteria for confirmation and the Equivalence Condition, the unintuitive conclusion that things like white roses, green T-shirts and ice cubes confirm the raven hypothesis 'All ravens are black.' By a small rearrangement of the Equivalence Condition, I show that we can also derive the conclusion, which sounds even more intuitively intolerable, that observation of black ravens fails to confirm the raven hypothesis. We are left with the contradictory result that black ravens both confirm and do not confirm the raven hypothesis.